Carbon emission and cost of blockchain mining in a case of peer-to-peer energy trading - Coutinho, Kevin; Wongthongtham, Pornpit; Abu-Salih, Bilal; Abu Saleh, Mousa A.; Khairwal, Neeraj Kumari (Frontiers in Built Environment, 2022)
Blockchain is an emerging technology that has demonstrated great uptake potential in Peer-to-Peer (P2P) energy trading. The revolution of blockchain brings substantial benefits and innovation to sustainability energy transitions through P2P trading. Blockchain enables energy commodities to be traded. However, perceptions of this technology’s impact on the environment and its associated costs have garnered recent adverse publicity. This paper aims to look at the linkages between blockchain technology and energy systems in terms of blockchain power consumption against blockchain advantage over renewable energy transitions via peer-to-peer energy trading. The amount of energy used and carbon released during the blockchain validation process is estimated, and the cost of blockchain is computed to assess its economic benefit in a peer-to-peer energy trading scenario. Real data from running peer-to-peer energy trading systems are used, and numerous insights on the transformation of peer-to-peer energy trading utilising various blockchain scaling methods are provided. Based on the analysis, this paper concludes that the cost of processing trading transactions is lower using blockchain than current coordination costs. Also, blockchain-based energy can be traded more frequently than current regulations allow in order to reap the full benefits of renewable energy. A secure blockchain-enabled P2P trading environment would lead to fair rates for energy providers and prosumers resulting in stimulating the renewable energy market.